Occurrence of protozoans & their limnological relationships in some ponds of Mathbaria, Bangladesh (University Journal of Zoology, Rajshahi University, 2012)
DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9470UJZRU 2010; 29(1): 69-71